DEVELOPING FINE MOTOR SKILLS USING THE EXPLICIT INSTRCUTION MODEL AND ASSIGNING TASKS IN CUTTING OUT GROUP B PATTERNS IN BAITUL MAKMUR ISLAMIC KINDERGARTEN BANJARMASIN - gina faudina; Novitawati Novitawati (E-CHIEF Journal, 2022)
AbstractThe purpose of this study was to determine the activities of educators, students and the results of children's development in cutting patterns. This study uses a qualitative approach with the type of Classroom Action Research (CAR) conducted in 3 meetings. The research subjects were group B of Baitul Makmur Integrated Islamic Kindergarten with 13 children. The use of the instrument is the activity sheet of educators, students, and developmental results. While the data analysis used descriptive analysis. The findings showed that teacher activity increased from meeting 1 with the criteria of "good enough" to the category of "very good" at meeting 3. The classical activities of children at the initial meeting were 53% with the criteria of "most of the children were active" to 92% with the criteria of "Almost All Children Very Active” at meeting 3. The results of classical child development at meeting 1 were 54% with the interpretation of BB (Not yet Developed) progressing up to 92% or with BSB interpretation at meeting 3. It is recommended to use the Explicit Instruction Model with the Assignment Method as a reference for effective learning to develop aspects of Children's fine motor skills, especially in the development of cutting according to patterns.Keyword: Explicit Instruction, Assignment, Cutting Patterns